DAMPAK KEBERADAAN TAMBANG BIJIH NIKEL PT TEKINDO ENERGI TERHADAP SOSIAL EKONOMI MASYARAKAT DESA WAIBULAN KECAMATAN WEDA TENGAH - Noviyanti Jainudin Abd Latif; Faisal Y Habsyi; Datje Renjaan (Program Studi Pendidikan Ekonomi Institut Sain dan Kependidikan (ISDIK) Kie Raha Maluku Utara, 2025)
The purpose of this study was to determine the impact of the presence of PT. Tekindo Energi's nickel ore mine on the socio-economic community of Waibulan, Weda Tengah District, using qualitative research with 25 respondents. The results of the study showed that the presence of the nickel mine in Waibulan village had a positive impact on unemployment and increased economic welfare of the community. However, this was temporary. In addition, the presence of the mine also had an impact on increasing community income and decreasing the unemployment rate. Therefore, the presence of PT. Tekindo Energi had a positive impact on socio-economic changes in the Waibulan community, Weda Tengah District.